2008
DOI: 10.1152/ajplung.00394.2007
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of store-operated Ca2+entry by CD38 in human airway smooth muscle

Abstract: (11,15,20,26,38,39,46) or by plasma membrane Ca 2ϩ influx.TNF␣, a potent proinflammatory cytokine found in bronchoalveolar lavage fluid (12) and sputum (50) from asthmatics, has been implicated as a mediator in the pathophysiology of asthma (45, 51, 52) and chronic obstructive pulmonary disease (8, 16). Indeed, TNF␣ has been shown to enhance ASM contractility (13,43,47 (11,20,46) as well as via ryanodine receptor (RyR) channels (15, 26), the latter resulting from increased levels of the novel second messenger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
77
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 59 publications
1
77
1
Order By: Relevance
“…TNF-a has been known to increase agonist-induced [Ca 21 ] i response and contractility in ASM (1,6,22,25). Our recent studies also showed that TNF-a increases SOCE in human ASM cells (11,22). Similarly, IL-13 enhances agonist-induced [Ca 21 ] i responses in human ASM (26), and increases airway contractility in mouse and rat tracheas (27).…”
Section: Clinical Relevancementioning
confidence: 89%
See 3 more Smart Citations
“…TNF-a has been known to increase agonist-induced [Ca 21 ] i response and contractility in ASM (1,6,22,25). Our recent studies also showed that TNF-a increases SOCE in human ASM cells (11,22). Similarly, IL-13 enhances agonist-induced [Ca 21 ] i responses in human ASM (26), and increases airway contractility in mouse and rat tracheas (27).…”
Section: Clinical Relevancementioning
confidence: 89%
“…Upon sensing SR Ca 21 depletion, STIM1 oligomerizes with adjacent STIM1 proteins via the SAM domain, and moves within the SR membrane to enhance its proximity to the PM, where STIM1 interacts with Orai1 and transient receptor potential cation channels to form clusters, thus activating these PM channels to induce SOCE (24). Although much of the information on STIM1 was derived from nonexcitable cells and expression systems, STIM1 has been demonstrated in human ASM cells, and is implicated in the regulation of [Ca 21 ] i responses (11,21,22). The knockdown of STIM1 results in reduced SOCE after store depletion, whereas the overexpression of STIM1 dramatically increases SOCE in human ASM cells (21).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro studies showed that CD38 expression and its enzymatic activities are increased by TNF-, IFN-, IL-1 and IL-13 ( Fig. 2) [93][94][95]. TNF--induced CD38 expression is transcriptionally regulated and involves NF-B-dependent andindependent mechanisms [96].…”
Section: Adp-ribose Cyclasesmentioning
confidence: 99%